The right to education for remand prisoners in Romanian penitentiaries: Bridging national law and European human rights - Curt, Ioana (Form@re - Open Journal per la formazione in rete, 2025)
This article examines the denial of the right to education to remand prisoners in Romanian penitentiaries, a practice contrary to the European Court of Human Rights (ECtHR) jurisprudence. It focuses on a recent ruling of the Bucharest District 5 Court, which compelled a prison to uphold this right based on ECtHR standards. The discussion highlights the legal landscape in Romania, relevant international recommendations, and advocates for formal recognition of this right for remand prisoners who have been indicted and transferred to penitentiary facilities. Il diritto all’istruzione per i detenuti in custodia cautelare in Romania: tra legge nazionale e diritti umani europei. Questo articolo esamina la negazione del diritto all’istruzione ai detenuti in custodia cautelare negli istituti penitenziari rumeni, una pratica contraria alla giurisprudenza della Corte Europea dei Diritti dell’Uomo (CEDU). La recente sentenza del Tribunale del Settore 5 di Bucarest, che si analizza nel Saggio, ha posto l’obbligo per un istituto di garantire il diritto all’istruzione in base agli standard della CEDU. La discussione evidenzia il quadro giuridico in Romania, le raccomandazioni internazionali pertinenti e sostiene il riconoscimento formale di questo diritto per i detenuti in custodia cautelare, imputati e trasferiti nelle strutture penitenziarie.